Development of technological desalination schememineralized water and material balance for engineering calculation of the installation - Тогабаев, Е.Т.; Утепбергенова, Л.М.; Молдабаева, Г.Н. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The problems of pollution of water sources and freshwater deficit can be solved by the development and introduction of environmentally friendly water treatment technologies, to which, in the first place, membrane technologies, including dialysis and electrodialysis. The proposed plant allows to obtain fresh water and to prevent the discharge of brines, which are used for the preparation of regeneration solutions for sodium cationite filters. The analysis of the material balance for the engineering calculation of the installation is carried out, and the resulting material balance allows the calculation of the content of certain components and the amount of solution in individual elements of the technological scheme. In developing the scheme, the following objectives were pursued: partial desalination (desalination) of mineralized waters to produce fresh water; liquidation of effluents and utilization of concentrated brine; reduction of reagents due to the use of brines for the preparation of regeneration solutions.